Foreign Direct Investment Dalam Pembangunan Ekonomi Indonesia Perspektif Ekonomi Islam: Foreign Direct Investment In Indonesia Economic Development, Islamic Economic Perspective - Lira Zohara (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
Indonesia is a development country that requires a large amount of funds to carry out development. To encourage development, Indonesia receives domestic and foreign financing. FDI (Foreign Direct Investment) is one of the alternative sources of funds in increasing development in Indonesia. FDI is a type of foreign investment that makes a significant contribution through asset transfers and management, as well as technology transfers that can boost the Indonesian economy. Investment in Islam is an activity based on this because of the investment, assets will be more productive and useful for others. The objective achieved in this study is to review how FDI in development is viewed from an Islamic economic perspective. In this study using the Library Research method, which is a study that utilizes library sources to obtain research data. Data obtained from books, papers or articles, magazines, journals, web (internet) or other information related to the title.